Biodiversity research in Malinau - Sheil, Douglas (CIFOR and ITTO, 2002)
This chapter reports on a range of research conducted in CIFOR's research area in Malinau, East Kalimantan. A major emphasis of this work was to begin to document the biological wealth of this area. The main task had three major aspects: 1) finding out what occurs where, 2) assessing to whom it matters and in what way, and 3) identifying how to maintain this biota in the future. These studies combined both biological and social aspects, in order to determine not only what species and habitats were present but also how local communities used and view them. Background data also characterises sites and soils in the wider landscape. Surveys were undertaken in seven communities with the full participation of the villagers. The survey established 200 plots on a wide range of vegetations, and collected a wide range of specimens and related information. The survey area of these community territories is about 2,000 km2. Preliminary results of this research are presented. Additional research activities include assessments of fish, of reptiles and amphibians. Baseline data for mammals, birds and some invertebrates are also reported from the main logging studies. Local communities are found to be very dependent on the forest in many ways. Over two thousand plant taxa were recorded and over one thousand species were found to have significant direct values. Many animals are also indirectly recorded and found to have value to the communities. The area is found to be very infertile, and few options for sustainable agriculture or plantations are viable due to poor soils, and steep terrain. Various suggestions for improved forest and land-use management are presented. The region is found to be very rich in biodiversity. Several new species are reported.